Two mechanisms of drought tolerance in cowpea - Mai-Kodomi, Y.; Singh, B.B.; Myers, O.; Yopp, J.H.; Gibson, P.J. (1999)
Twelve cowpea (Vigna unguiculata) varieties were planted in wooden boxes of 130 cm length, 65 cm width, and 15 cm depth filled with sand and soil mixture (1:1) at 10 cm row to row and 5 cm plant-to-plant distances. The boxes were watered daily until the unifoliate leaves had fully expanded and the first trifoliates were beginning to emerge. Watering was then stopped to impose moisture stress, and effects of drought on the unifoliate and trifoliate leaves as well as growing tips were studied. Two types of drought tolerance mechanisms were observed. Under drought stress Type 1 drought tolerant lines TVu 11986 and TVu 11979 stopped growth and conserved moisture in all the plant tissues, stayed alive for over two weeks and gradually the entire plant parts dried together. The Type 2 drought tolerant lines like Dan Ila and Kanannado continued slow growth of the trifoliates. However, with continued moisture stress, the unifoliates of these varieties showed early senescence and dropped off but the growing tips remained turgid and alive for longer, suggesting that moisture was being mobilized from the unifoliates to the growing tips